A useful demonstration of calculus in a physics high school laboratory. (3rd November 2017) - Alvarez, Gustavo; Schulte, Jurgen; Stockton, Geoffrey; Wheeler, David
Abstract: The real power of calculus is revealed when it is applied to actual physical problems. In this paper, we present a calculus inspired physics experiment suitable for high school and undergraduate programs. A model for the theory of the terminal velocity of a falling body subject to a resistive force is developed and its validity tested in an experiment of a falling magnet in a column of self-induced eddy currents. The presented method combines multiple physics concepts such as 1D kinematics, classical mechanics, electromagnetism and non-trivial mathematics. It offers the opportunity for lateral as well as project-based learning.